A late Pleistocene to Holocene archaeological record from East Kalimantan, Borneo. (1st February 2022) - Maloney, Tim Ryan; Dilkes-Hall, India Ella; Setiawan, Pindi; Oktaviana, Adhi Agus; Geria, I. Made; Effendy, Muslimin; Ririmasse, Marlon; Febryanto,; Sriputri, Etha; Priyatno, Andika; Atmoko, Falentinus Triwijaya; Moffat, Ian; et al.
Abstract: Recent archaeological excavations at Liang Jon, a limestone rockshelter in the East Kalimantan province of Indonesian Borneo, have revealed a cultural sequence covering the period from around 16, 700 calibrated radiocarbon years before present (16.7 kyr cal BP) until the late Holocene—a time of dynamic environmental, social, and economic change throughout Island Southeast Asia. There are few published archaeological sequences from this period of human history from Borneo, a geographically strategic region in the wider early human settlement of the region, highlighting the importance of our initial finds and dating work at Liang Jon. We describe our excavation and present chronostratigraphic and initial summary data to outline the significance this cultural sequence has in reconciling archaeological evidence and dated rock art records from early human cultural behaviour at the easternmost margin of the Late Pleistocene continental landmass of Sunda. Summary data, including stone artefacts, marine shell beads, faunal remains, and a pre-Austronesian burial, contributes to our understanding of regional trends associated with widespread cultural and technological change during the Pleistocene to Holocene transition, when the present-day island of Borneo was formed. Highlights: Archaeological excavations reveal rich cultural sequence spanning 16.7 kyr cal BP in Borneo. Assemblage partially overlaps with dated rock art from the same region of Borneo. Technological and subsistence adaptation by artistic people thriving in the post-LGM world. Archaeological sequence contributes to widespread regional change in the early Holocene. First Hoabinian and microlith stone tools documented from early Holocene Borneo.